=    1/6   -  2/3

44)

=    1/3   -  4/6

45)

=    2/3  +  2/6

46)

=    2/5  +  5/10

47)

=    3/9  + 

48)

=        -   5/8

49)

=    6/7  +  4/9

50)

=    1/3  +  3/8

51)

=    1/3  +

52)

=    1/3  - 

53)

=    2/3  - 

54)

=    2/9  - 

55)

=    2/3  -  8/9

56)

=    1/3  -  2/6

57)

=    1/3  -  7/21

58)

=    4/6  -  5/7

59)

=   2/10 + 3/5

60)

=   1/3   +  1/9

61)

=        -  3/8

62)

=  1/6    -  2/3

63)

=  3/7   +  1/5

64)

=  6/8   + 

65)

=  1/3   +  1/9

66)

=  1/5   -   3/5

67)

=  3/10 -  4/5

68)

=  2/7  +  5/9

69)

=  2/3  +  1/3

70)

=  2/3  -  5/6

71)